Development of 3D models and animations for VR/AR - Lu, Yawen (2018)
Nowadays, Virtual Reality (VR) and Augmented Reality (AR) technologies are rapidly emerging fields which can provide an immersive 3D experience and the potential to improve human abilities in learning, training and cognition in complex environments. The task of this dissertation project is to try to develop a VR/AR application for classroom teaching to offer students better understanding and more direct feelings towards complex polarization wave models. The tasks of this project are in 3 parts: Firstly, research preparation, where 3 types of polarized waves are introduced and their wave equations are deduced. The principles and components of VR and AR are also analyzed. Secondly, the experimental process and their results; this involves constructing 3D animation models for wave polarization, rendering VR and AR effects with support packages, and exporting the applications to different mobile devices. Thirdly, tests and evaluation of visual and display performances. By comparing performance with other existing methods and applications, the aim is to propose some possible improvements. Through this project, the author will have a more profound understanding of the imaging signal field; as to how the VR/AR devices and 3D TV work; and how to construct and render a 3D animation model. He will acquire a basic understanding of the process of preparing, making, testing, evaluating and publishing an application and product. This will include how to make the application more flowing and user-friendly, and give solutions for dealing with compatibility problems among different systems and devices. In addition, it will assist the author to improve his problem-solving abilities and programming skills. Keywords: VR Application; AR Application; EM Polarization; Classroom Teaching;